Secondary school pupilsʼ experiences of participating in adapted farm-based education in Norway<subtitle>Inner motivation and personal development outcomes</subtitle> - Siv Merete Kjenes Arnesen (Nordisk Tidsskrift for Ungdomsforskning)
The Norwegian government approves farm-based education for pupils who do not benefit sufficiently from ordinary school. The aim of this article is to contribute knowledge on secondary school pupilsʼ experiences of such programs, and how they affect inner motivation for school. The article is based on qualitative interviews with thirteen pupils in years nine and ten (ages 14-16) from farms located in different regions of Norway. The pupils experienced the farmersʼ care and involvement, became part of a safe and inclusive community, were given the opportunity to try varied practical activities, experienced personal development, and gained new motivation for school. Using basic psychological needs theory and recovery theory, it is found that the pupils experienced relatedness to other pupils and to the farmers, improved their social and practical competence, and experienced autonomy (self-determination) through voluntary participation. The farmers and the community can be described as autonomy-supportive and “restitution-nourishing” and as contributing to personal development and the development of inner motivation. This strengthened the pupilsʼ self-confidence, hope for the future, and their attention in and efforts at school. The findings from the study indicate that motivation developed in one learning context (the farm) can influence the motivation for another context (ordinary school).